PERFORMANCE EVALUATION OF SINGLE-PATH AND MULTIPATH MANETS ROUTING PROTOCOLS FOR DENSE AND SPARSE TOPOLOGY - Mahdi, Mohammed A.; Wan, Tat Chee (Penerbit Universiti Malaysia Pahang, 2017)
Mobile Ad Hoc Network (MANET) is a multi-hop wireless network in which fixed infrastructure is not used. A single-path routing protocol is mainly proposed as a single route from source node to destination node, while a multipath routing protocol uses multiple routes from the source to the destination node. This paper evaluates the performance of single-path routing protocols which are Cluster Based Routing Protocol (CBRP) and Ad hoc On-demand Distance Vector (AODV) along with a multipath routing protocol which is Ad hoc On-demand Multipath Distance Vector routing (AOMDV) in MANET environments with varying node densities (Dense and Sparse). Network Simulator (NS2) was used to evaluate the performance of these routing protocols. Our experimental simulation results show that: AOMDV protocol is better than AODV and CBRP in terms of Delay for both Dense and Sparse topologies with variant traffic sources, whereas AODV is better than CBRP and AOMDV in terms of Packet Delivery Ratio (PDR) with all traffic sources in Sparse topology.